Needs Analysis for a STEM-Based Interactive E-Worksheet Using Heyzine and Problem-Based Learning in Elementary Mathematics - Mutiara Rachmadini; Neza Agusdianita; Agus Susanta; Ade Gusti Ningsih (AL-ISHLAH: Jurnal Pendidikan, 2025)
Mathematics instruction in Indonesian elementary schools often relies on conventional, text-heavy worksheets that lack interactivity and contextual relevance. These limitations hinder students’ engagement, problem-solving development, and alignment with 21st-century competencies and Profil Pelajar Pancasila (P3). This study aims to identify the needs of teachers and students for a STEM-based, interactive E-Worksheet using Heyzine integrated with Problem-Based Learning (PBL). An exploratory sequential mixed-methods design was employed as the initial phase of a broader design-based research cycle. Quantitative data were collected from 22 fifth-grade teachers and 110 students across 11 public elementary schools in Bengkulu City through validated questionnaires. Qualitative insights were obtained from semi-structured interviews with five teachers. Data were analyzed using descriptive statistics and thematic coding. Findings reveal that less than half of students (47.27%) found existing worksheets clear and engaging. Teachers rated the current modules at 40–45% across core indicators, citing weak integration of STEM-PBL principles, low interactivity, and insufficient alignment with P3 values. Both students and teachers emphasized the need for multimedia-rich, contextually relevant materials that support inquiry and collaboration. The study highlights a significant gap between curricular goals and actual classroom practices. It underscores the urgency of developing interactive, multimodal digital worksheets using platforms like Heyzine to enhance student engagement, problem-solving skills, and teacher readiness for digital pedagogy.